Azimuthal decomposition study of a realistic laser profile for efficient modeling of Laser WakeField Acceleration. (July 2020) - Zemzemi, I.; Massimo, F.; Beck, A.
Abstract: The advent of ultra short high intensity lasers has paved the way to new and promising, yet challenging, areas of research in the laser-plasma interaction physics. The success of constructing petawatt femtosecond lasers, for instance the Apollon laser in France, will help understanding and designing future particle accelerators and next generation of light sources. Achieving this goal intrinsically relies on the combination between experiments and massively parallel simulations. So far, Particle-In-Cell (PIC) codes have been the ultimate tool to accurately describe the laser-plasma interaction especially in the field of Laser WakeField Acceleration (LWFA). Nevertheless, the numerical modelling of laser plasma accelerators in 3D can be a very challenging task. This is due to the large dispersity between the scales involved in this process. In order to make such simulations feasible with a significant speed up, we need to use reduced numerical models which simplify the problem while retaining a high fidelity. Among these models, Fourier field decomposition in azimuthal modes for the cylindrical geometry [1] is a promising reduced model especially for physical problems that have close to cylindrical symmetry which is the case in LWFA. This geometry has been implemented in the open-source code SMILEI [2] in Finite Difference Time Domain (FDTD) discretization scheme for the Maxwell solver. In this paper we will study the case of a realistic laser measurement from Apollon facility, the ability of this method to describe it correctly and the determination of the necessary number of modes for this purpose. We will also show the importance of higher modes inclusion in the case of realistic laser profiles to insure fidelity in simulation.